World Economic Outlook, May 1990. (World Economic Outlook; World Economic Outlook ;, 1990)
This paper highlights that world economic activity slowed in 1989 to about 3 percent from an exceptionally rapid rate of 4 percent in 1988. The growth of output is expected to moderate further in 1990, to 2u percent, before picking up to about 3 percent in 1991. The slowdown reflects the restrictive monetary policies that have been implemented in most industrial countries to deal with pressures on productive capacity and rising inflation. Output growth is expected to decline further in 1990 in North America and the United Kingdom.